Nitrogen response models for winter cereals grown for forage. (25th October 2018) - Lyons, Sarah E.; Tang, Zhehan; Booth, James; Ketterings, Quirine M.
Abstract: Forage double cropping can increase production, reduce erosion risk and improve soil health. Farmer experience in the north‐eastern USA shows that winter cereals can, in 3–4 weeks (Feekes 9 harvest), produce high quality forage given sufficient N at dormancy break. Here, we evaluate crop response models to determine the most economic rate of N (MERN) for forage winter cereals. Sixty‐three on‐farm N‐rate trials (0, 34, 67, 101, 135 kg N/ha) were conducted in New York from 2013 to 2016. Trials were divided into four categories: (a) no yield response to N (group 1; 20 trials); (b) yield plateau exceeded the highest N rate (group 2; one trial); (c) the MERN was below the lowest N rate (group 3; seven trials) and (d) all other N‐responsive trials (group 4; 35 trials). For group 4, three statistical models were compared (quadratic plateau, exponential and square root plateau). Statistical, environmental and economic criteria showed that the quadratic plateau fits the data best and had the most stable predictions across scenarios. The four‐category analysis is effective in determining MERNs of individual trials, and the quadratic plateau is best for determining forage winter cereal MERNs and yields at MERNs for individual trials in the north‐eastern USA.